The comparable body : analogy and metaphor in ancient Mesopotamian, Egyptian, and Greco-Roman medicine - Wee, John Z. (Studies in Ancient Medicine, 2017)
The Comparable Body - Analogy and Metaphor in Ancient Mesopotamian, Egyptian, and Greco-Roman Medicine explores how analogy and metaphor illuminate and shape conceptions about the human body and disease, through 11 case studies from ancient Mesopotamian, Egyptian, and Greco-Roman medicine. Topics address the role of analogy and metaphor as features of medical culture and theory, while questioning their naturalness and inevitability, their limits, their situation between the descriptive and the prescriptive, and complexities in their portrayal as a mutually intelligible medium for communication and consensus among users.